2022
DOI: 10.1155/2022/7366063
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Professional and Patient Satisfaction with Telerehabilitation of Musculoskeletal Disorders: A Systematic Review

Abstract: Telerehabilitation offers an alternative healthcare delivery remotely in a patient’s environment at a lower cost, better accessibility, and equivalent quality to the standard approach. Several studies had examined the effectiveness of telerehabilitation inpatients with musculoskeletal disorders, and although there is evidence that it is at least equally effective as the standard care, the patient and rehabilitation professional satisfaction with the delivery method is not conclusive. A systematic review was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…According to Salazar Fernandez et al, 26 T‐Med allows accurate diagnosis and treatment for most TMD cases, shortens treatment time delays and lowers unnecessary costs for TMD patients. This was similar the findings of existing literature 27,28 . Ricea Chairunnisa et al promoted efficacy through self‐management by using jaw exercised videos with reminders 18 .…”
Section: Discussionsupporting
confidence: 89%
“…According to Salazar Fernandez et al, 26 T‐Med allows accurate diagnosis and treatment for most TMD cases, shortens treatment time delays and lowers unnecessary costs for TMD patients. This was similar the findings of existing literature 27,28 . Ricea Chairunnisa et al promoted efficacy through self‐management by using jaw exercised videos with reminders 18 .…”
Section: Discussionsupporting
confidence: 89%
“…In comparison with traditional rehabilitation, only two studies carried out an analysis of efficacy [31,33], both of which position it as equally effective, and even superior in some parameters such as SGRQ [31]; although more studies are needed on this population, telerehabilitation already has a more than proven efficacy in other pathologies [18,43,44] as well as a much lower cost [45,46] and a good reception by patients [24,47]. These aspects make telerehabilitation a new trend in health sciences and, more specifically, boosted by the COVID-19 pandemic [48].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that patient satisfaction with an intervention is influenced by the results obtained, the patient–provider interaction, 21 and in the case of a digital intervention by the quality of the technology used. 63 Furthermore, the ability of professionals to adapt to new technologies and adopt them in their practice must be considered. More research addressing digital health training for both providers and patients is needed for better implementation.…”
Section: Discussionmentioning
confidence: 99%